Implementing key performance indicators in a government agency: a typical story? - Laurence, Ferry; Murphy, Peter; Zakaria, Zamzulaila; Zakaria, Zarina (Chartered Institute of Public Finance and Accountancy (CIPFA), 2015)
The main objective of this study is to provide insight into the implementation of Key Perfor- mance Indicators (KPIs) in public sector organisations. Drawing on a case study of a govern ment agency that is responsible for providing training and financial assistance to students and entrepreneurs in Malaysia we suggest that adoption of KPIs can be instrumental, but is also isomorphic, following management fashion, and has been used for legitimisation. Implementation of KPIs requires strong support, both human and non-human, if their introduction is to be effective. The key to perceived effectiveness of KPIs in this study lay primarily within the role of champions who were able to convince and convert members of the organisation of the value of KPIs to their activities.